PENDAMPINGAN PENGEMBANGAN BISNIS DENGAN IMPLEMENTASI STRATEGI BISNIS MODEL CANVAS PADA CLOTHING DISTRO PAUL – SURABAYA - Citra Anggraini Tresyanto; Stephanie Astrid Ayu; V. Devina Setyawati; Maria Angelina Susilo (LPPM Universitas Bina Bangsa, 2024)
Currently, the world of fashion sells a lot via e-commerce. The main cause of this condition is the fashion world's target consumers who focus on the productive age group, namely 15 - 64 years old. However, for young people's fashion, many people aged 15 - 40 are looking at it. This condition then led to the growth of very tight fashion competition. Therefore, fashion businesses need to design a systematic business strategy to ensure the sustainability of their business. One of the business ventures that is facing the current competitive situation with fashion is Paul Distro Clothing. Focusing on men's clothing products, namely t-shirts with character motifs, are the main products. Paul Distro Clothing is one of the business actors who is facing competition in the fashion business, such as the emergence of new competitors with the same products, thrift products which are being loved by young people. This assistance is also needed so that business continuity continues well. The output target of this community service activity is to increase knowledge of partners' business strategies as a business sustainability effort.